Makna Kultural dalam Tradisi Mendhem Ari-Ari di Desa Candisari Kabupaten Grobogan - Ananda Dwi Rahayu; Naurah Nadzifah Ramadhani; Imam Baehaqie (Universitas Sultan Ageng Tirtayasa, 2026)
This study examines the cultural significance of the Mendhem Ari-Ari tradition in Candisari Village, Grobogan Regency. It focuses on two main aspects: the verbal and nonverbal aspects that emerge during the tradition. Using a cultural semantics, semiotics, and etnolinguistics framework, the study attempts to understand how symbols, actions, and utterances within the tradition reflect the perspectives and cultural values of the local community. Data were collected through direct interviews, recordings, and note-taking, with the Candisari Village community as the primary source. Of the 22 items collected, 21 are nonverbal and only one is verbal. Analysis using the matching method shows that each element of the Mendhem Ari-Ari tradition has a meaning related to hopes for safety, protection, and prayers for the growth and future of newborns. This tradition ultimately demonstrates how the community maintains cultural values through inherited symbols and practice.